High entropy alloying strategy for accomplishing quintuple-nanoparticles grafted carbon towards exceptional high-performance overall seawater splitting - Raj, Gokul; Nandan, Ravi; Kumar, Kanhai; Gorle, Demudu Babu; Mallya, Ambresh B.; Osman, Sameh M.; Na, Jongbeom; Yamauchi, Yusuke; Nanda, Karuna Kar (Royal Society of Chemistry, 2023)
High entropy alloys (HEAs), a novel class of material, have been explored in terms of their excellent mechanical properties. Seawater electrolysis is a step towards sustainable production of carbon-neutral fuels such as H2, O2, and industrially demanding Cl2. Herein, we report a practically viable FeCoNiMnCr HEA nanoparticles system grafted on a conductive carbon matrix for promising seawater electrolysis. The comprehensive kinetics analysis of the hydrogen evolution reaction (HER), oxygen evolution reaction (OER), and chlorine evolution reaction (CER) confirms the effectiveness of our system. As an electrocatalyst, HEAs grafted on carbon black show trifunctionality with promising kinetics, selectivity and enduring performance, towards seawater splitting. We optimize high entropy alloy decorated/grafted carbon black (HEACB) catalysts, studying their synthesis temperature to scrutinize the effect of alloy formation variation on the catalysis efficacy. During the catalysis, selectivity between two mutually competing reactions, CER and OER, in the electrochemical catalysis of seawater is controlled by the reaction media pH. We employ Mott-Schottky measurements to probe the band structure of the intrinsically induced metal-semiconductor junction in the HEACB catalyst, where the carrier density and flat band potential are optimized. The HEACB sample provides promising results towards overall seawater electrolysis with a net half-cell potential of about 1.65 V with good stability, which strongly implies its broad practical applicability. Novel carbon materials with grafted high-entropy alloying quintuple nanoparticles exhibit multifunctionality in seawater splitting, including catalysis for hydrogen evolution reactions, oxygen evolution reactions, and chlorine evolution reactions.